Haeme oxygenase-1 and cardiac anaphylaxis - Ndisang, Joseph Fomusi (2001)
1. Haeme oxygenase (HO) is an enzyme mainly localized in the smooth endoplasmic reticulum and involved in haeme degradation and in the generation of carbon monoxide (CO). Here we investigate (1) whether the inducible isoform of HO (HO-1) is expressed in the isolated heart of the guinea-pig and (2) the functional significance of HO-1 on the response to antigen in isolated hearts taken from actively sensitized guinea-pigs. 2. Both the HO-1 expression and activity are consistently increased in hearts from guinea-pigs pretreated with hemin, an HO-1 inducer (4 mg kg(−1) i.p., 18 h before antigen challenge). The administration of the HO-1 inhibitor zinc-protoporphyrin IX (ZnPP-IX, 50 μmol kg(−1), i.p., 6 h before hemin) abolished the increase of both the HO-1 expression and activity. 3. In vitro challenge with the specific antigen of hearts from actively sensitized animals evokes a positive inotropic and chronotropic effect, a coronary constriction followed by dilation and an increase in the amount of histamine in the perfusates. In hearts from hemin-pretreated animals, antigen challenge did not modify the heart rate and the force of contraction; the coronary outflow was significantly increased and a diminution of the release of histamine was observed. The patterns of cardiac anaphylaxis were fully restored in hearts from animals treated with ZnPP-IX 6 h before hemin. 4. In isolated hearts perfused with a Tyrode solution gassed with 100% CO for 5 min and successively reoxygenated, the response to antigen was similar to that observed in hearts from hemin-pretreated animals. 5. Pretreatment with hemin or the exposure to exogenous CO were linked to an increase in cardiac cyclic GMP levels and to a decrease of tissue Ca(2+) levels. 6. The study demonstrates that overexpression of HO-1 inhibits cardiac anaphylaxis through the generation of CO which, in turn, decreases the release of histamine through a cyclic GMP- and Ca(2+)-dependent mechanism.